Nanomaterial-based biosensors: a new frontier in plant pathogen detection and plant disease management - Narware, Jeetu; Chakma, Jharjhari; Singh, Satyendra P.; Prasad, Divya Raj; Meher, Jhumishree; Singh, Prachi; Bhargava, Priya; Sawant, Shraddha Bhaskar; Pitambara,; Singh, Jyoti P.; Manzar, Nazia; Kashyap, Abhijeet Shankar (Frontiers in Bioengineering and Biotechnology, 2025)
Nanotechnology has significantly advanced the detection of plant diseases by introducing nano-inspired biosensors that offer distinct advantages over traditional diagnostic methods. These biosensors, enhanced with novel nanomaterials, exhibit increased sensitivity, catalytic activity, and faster response times, resulting in improved diagnostic efficiency. The increasing impact of climate-induced stress and emerging plant pathogens have created an urgent demand for real-time monitoring systems in agriculture. Nanobiosensors are revolutionizing plant disease management by enabling on-site detection of pests and weeds, facilitating precise pesticide applications. This article provides a comprehensive overview of the development and application of nanobiosensors in real-time plant disease diagnosis. It highlights key innovations, such as smartphone-integrated nanozyme biosensing and lab-on-a-chip technologies. Special emphasis is placed on the detection of molecular biomarkers, demonstrating the critical role of nanobiosensors in addressing the evolving challenges of plant disease management and agricultural sustainability.